Myeloid-derived suppressor-like cells – a potential biomarker for prognosis of colorectal cancer? - Brčerević, Irina; Doder, Radoje; Vojvodić, Danilo; Perišić, Nenad; Petrović, Stanko (Vojnosanitetski pregled, 2023)
Background/Aim. Myeloid-derived suppressor cells (MDSCs) represent a heterogeneous group of immature cells that have the ability to inhibit both the innate and adaptive immune response. Due to their immunosuppressive effect, MDSCs can promote the growth and progression of cancer. Colorectal cancer (CRC) is one of the most common cancers in the general population for whose advanced stages there is still no successful therapy. In addition to contributing to the development and spread of CRC, MDSCs could potentially be seen as markers of its prognosis. The aim of the study was to examine the potential prognostic role of peripheral blood MDSC counts in CRC patients. Methods. This prospective study analyzed the possibility of using CD16low granulocytes and monocytic MDSC (M-MDSC) like cells, as well as neutrophil-to-lymphocyte ratio (NLR), lymphocyte-to-monocyte ratio (LMR), CD16high/CD16low granulocytes ratio, and monocyte-to-M-MDSC like cells ratio, before the start of the treatment, as biomarkers for overall survival (OS) in patients with CRC. The hazard ratio with the corresponding confidence interval of 95% (95% CI) was calculated to evaluate the prognostic role of MDSC in CRC. Results. The analysis was performed in 47 patients with stages III and IV of CRC according to the TNM/AJCC disease classification. Reliable data were obtained from 32 patients. Patient blood samples were taken before the possible start of treatment (surgery, chemotherapy). Increased percentages and absolute values of CD16low granulocytes, as well as absolute values of M-MDSC like cells, were associated with shorter OS (p < 0.0066, p < 0.0013, and p < 0.0119, respectively). The relationship between CD16high/CD16low granulocytes ratio and monocyte/M-MDSC like cells ratio with OS indicated the existence of positive correlations between these parameters, where the higher value of this relationship indicated longer OS of patients (p < 0.0054 and p < 0.0148, respectively). The relationship between OS and NLR showed a statistically significant inverse correlation (p = 0.0349). No statistical significance was found in the relationship between OS and LMR. Conclusion. Percentages and absolute numbers of CD16low granulocytes, as well as the absolute numbers of M-MDSC like cells, the CD16high/CD16low granulocytes ratio, monocyte/M-MDSC like cells ratio, and NLR ratio, may be reliable indicators of OS in patients with CRC.
Keywords: biomarkers; colorectal neoplasms; myeloid-derived suppressor cells; prognosis; treatment outcome